A comparative study on the bendability of a dual phase steel: three-point bend versus V-die test - Nizia Mendes-Fonseca; Mahmoud Diab; Jidong Kang; David S. Wilkinson (Journal of Materials Research and Technology)
The bendability of materials can be assessed using a range of standard tests, which are distinguished by their configuration, especially the presence or absence of a die and the span between the support rollers or die shoulders. However, the effects of the bending configuration on the strain distributions have not been systematically studied. Here, we report on a comparative study of bend tests performed on a dual phase steel using three-point bend and V-die test configurations via both experiments and finite element modelling. The strains at the outer surface of the samples were measured using the digital image correlation technique. It is shown that the deformation and fracture are remarkably different in the two testing setups. The three-point configuration results in higher strain levels due to its shorter span, and the drawing and coining stages in V-die bending cause a sharp increase in the tangential strain and effectively eliminate springback. Higher strains are observed for small punch radii, but the strain evolution slows for large punch radii due to the change in the bending configuration from three-to four-point bending as the material folds over the punch.